Determinan Kepuasan Kerja Karyawan Pada PT. X Medan - Bagus Handoko (JURNAL ILMIAH MANAJEMEN & BISNIS, 2014)
This research aimed to find out the correlation between motivation  and compensation  to employee satisfaction. Simultaneously motivation  and compensation had positive influence on employee satisfaction.  Partially, motivation had positive influence to satisfaction, but compensation had no influence to satisfaction. That means that company have to increase employee satisfaction that can be increasing employee performance.